2008
DOI: 10.3858/emm.2008.40.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Nur77 upregulates HIF-α by inhibiting pVHL-mediated degradation

Abstract: In this study, we investigated the role of Nur77, an orphan nuclear receptor, in HIF-α transcriptional activity. We found that Nur77 associates and stabilizes HIF-1α via indirect interaction. Nur77 was found to interact with pVHL in vivo via the α-domain of pVHL. By binding to pVHL, Nur77 competed with elongin C for pVHL binding. Moreover, Nur77-binding to pVHL inhibited the pVHL-mediated ubiquitination of HIF-1α and ultimately increased the stability and transcriptional activity of HIF-1α. The ligand-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 39 publications
(53 reference statements)
2
32
0
Order By: Relevance
“…4,5,[29][30][31][32][33] Moreover, some bcl-2 protein interactors, such as the bcl-2 mitochondrial chaperone FKBP38, the orphan nuclear receptor Nur77 and the molecular chaperone HSP90, have been demonstrated to be involved in oxygen-dependent and -independent regulation of the HIF-1a protein. [33][34][35] Even if we recently demonstrated that bcl-2 protein under hypoxic conditions interacts with both HIF-1a and HSP90 proteins contributing to the enhancement of HIF-1a protein stability, 21 we cannot exclude that also other bcl-2 interactors can be involved in bcl-2-induced HIF-1a/VEGF regulation.…”
Section: Discussionmentioning
confidence: 94%
“…4,5,[29][30][31][32][33] Moreover, some bcl-2 protein interactors, such as the bcl-2 mitochondrial chaperone FKBP38, the orphan nuclear receptor Nur77 and the molecular chaperone HSP90, have been demonstrated to be involved in oxygen-dependent and -independent regulation of the HIF-1a protein. [33][34][35] Even if we recently demonstrated that bcl-2 protein under hypoxic conditions interacts with both HIF-1a and HSP90 proteins contributing to the enhancement of HIF-1a protein stability, 21 we cannot exclude that also other bcl-2 interactors can be involved in bcl-2-induced HIF-1a/VEGF regulation.…”
Section: Discussionmentioning
confidence: 94%
“…Ubiquitination of HIF-1α is mediated by interaction with von Hippel-Lindau tumor suppressor protein (pVHL) (Kim et al, 2008). HIF-1α is targeted for VHL E3 ligase complex by proline hydroxylation of oxygen-dependent degradation (ODD) domain (Semenza, 2001;Safran and Kaelin, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Another important non-genomic function of NR4A1 appears to be the stabilization of hypoxia-inducible factor-1a (HIF-1a) under non-hypoxic conditions [56]. In normoxia, the a subunit of transcription factor HIF-1 becomes rapidly degraded through the ubiquitin-proteasome pathway [57].…”
Section: Nr4a1 As a Regulator Of Protein Stabilitymentioning
confidence: 99%
“…(as well as NR4A2) has the ability to bind the a domain of the von Hippel-Lindau (VHL) tumor suppressor, thereby preventing oxygen-dependent VHL-mediated proteasomal degradation of HIF-1a [56]. On the other hand, it has been reported that HIF-1 directly binds to the promoter of NR4A1 and enhances its expression under hypoxic conditions [58].…”
Section: Nr4a1 As a Regulator Of Protein Stabilitymentioning
confidence: 99%